Perceived glossiness in high dynamic range scenes - Doerschner, Katja (J Vis, 2010)
We investigated how spatial pattern, background, and dynamic range affect perceived gloss in brightly lit real scenes. Observers viewed spherical objects against uniform backgrounds. There were three possible objects. Two were black matte spheres with circular matte white dots painted on them (matte-dot spheres). The third sphere was painted glossy black (glossy black sphere). Backgrounds were either black or white matte, and observers saw each of the objects in turn on each background. Scenes were illuminated by an intense collimated source. On each trial, observers matched the apparent albedo of the sphere to an albedo reference scale and its apparent gloss to a gloss reference scale. We found that matte-dot spheres and the black glossy sphere were perceived as glossy on both backgrounds. All spheres were judged to be significantly glossier when in front of the black background. In contrast with previous research using conventional computer displays, we find that background markedly affects perceived gloss. This finding is surprising because darker surfaces are normally perceived as glossier (F. Pellacini, J. A. Ferwerda, & D. P. Greenberg, 2000). We conjecture that there are cues to surface material signaling glossiness present in high dynamic range scenes that are absent or weak in scenes presented using conventional computer displays.